Análisis de semilleros de investigación en cuanto a la deserción: programa de contaduría pública de la Universidad Santo Tomás de Tunja (2017)
The article will show the result of an investigation, carried out in Santo Tomás University (Tunja, Boyaca), which analyses the factors that have affected the dropout of students that took part in the research network in the Public AccountingProgram of the Faculty of Administrative Sciences and Accounting. By means of a qualitative-quantitative methodology applied to human and social sciences, it is evidenced that the active participation of students within the network has been incipient owing to the different internally and externally derived factors that are studied in the text.